Application of Exponentially Fitted Collocation Algorithm for Solving nth-Order Fredholm Integrodifferential Equations - Iyanda, Falade Kazeem; Omotayo Adebayo, Taiwo (Journal of Science and Technology, 2023)
In this paper, we seek to build and apply an exponentially fitted collocation algorithm (EFCA) for the solutions of nth-order Fredholm type integrodifferential equations. For this purpose, an EFCA was formulated and applied to solve four examples from the literature. Numerical experiment was performed and the results were compared with the exact solutions, and some existing methods. From the four examples considered, the results obtained showed that the proposed algorithm is fast, efficient, and reliable.